South Africa, Sweden, and Good International Citizenship - Suzanne Graham (The Thinker)
There are those who argue that a state embodying good international citizenship (GIC) must actively seek to improve the world around it, thereby making a positive contribution to overcoming global challenges. A good international citizen (state) must also be a proponent of multilateral cooperation, usually manifesting in global platforms such as the United Nations (UN). Scholars refer to middle power states being ideally situated in the power rankings of international affairs, respected by major and minor powers, to become custodians of emerging international norms and to pave a pathway forward for the community of states. Both South Africa and Sweden are seen as pivot countries in their respective regions and have a long history of shared desires and supports for freedom. This article will explore the notion of GIC and its desirability, and applicability, in relation to South Africa and Sweden. It employs a case study methodology approach in its research design and interrogates the extent to which South Africa and Sweden qualify as good international citizens according to four characteristics, drawn from the literature. The article finds that both Sweden and South Africa demonstrate elements of good international citizenship.